Psychological readiness to return to sports practice and risk of recurrence: Case studies - Gomez-Espejo, Veronica; Olmedilla, Aurelio; Abenza-Cano, Lucia; Garcia-Mas, Alejandro; Ortega, Enrique (Frontiers in Psychology, 2022)
Returning to sport after the sports injury is a difficult decision because it’s multicausal and the fact that a rash decision can result in numerous negative consequences. Given the importance of psychological variables for the correct rehabilitation of the injured athlete and his or her optimal return to sports practice, there seems to be little information on this subject. In this sense, the objective is to determine the relationship between the subjective psychological disposition of the athlete in the process of Return to Play (RTP) with the type of mood profile and his mental health. This is based on the fact that each athlete evaluates his or her recovery differently and has different levels of anxiety, depression and stress. For this purpose, four athletes participated in the study. 2 males and 2 females from the sports of indoor soccer and soccer, who had just returned to sports after a moderate or severe injury. The average age was 24.25 years. Various measurements were taken after practices and after matches, to assess mood, psychological readiness, anxiety, stress and depression. The results confirm Morgan’s iceberg profile and the influence that subjective psychological perceptions and assessed emotional states have on athletes’ incorporation into their sports practice with a guarantee of success.